Pharmacokinetics, absorption, distribution, metabolism and excretion of the MEK inhibitor zapnometinib in rats - Füll, Yvonne; Wallasch, Christian; Hilton, Ashley; Planz, Oliver (Frontiers in Pharmacology, 2022)
Zapnometinib is a MEK inhibitor currently under clinical development for the treatment of COVID-19 and influenza. Zapnometinib has both antiviral and immunomodulatory effects. Information concerning the absorption, distribution, metabolism, and excretion of the compound following single oral doses of 30 mg/kg [14C]-zapnometinib to rats was required to support pharmacology and toxicology studies in animals and clinical studies in man. As part of the development and safety assessment of this substance, zapnometinib was radioactively labeled and used for the investigation of time-dependent plasma concentrations, the rates and routes of excretion, the extent and time-course of compound distribution in body tissues, the metabolite profiles in plasma, urine and feces and the chemical nature of its metabolites. The present study reveals a rapid but low absorption of zapnometinib from the gastrointestinal tract, with more than 90% of the compound being excreted within 48 hours, mainly via feces. Whole body autoradiography confirms that zapnometinib was rapidly and widely distributed, with greatest concentrations in the circulatory and visceral tissues. Maximum plasma and tissue concentrations occurred between two and eight hours post dose. Penetration into the brain was low, and elimination from most tissues almost complete after 168 hours. Metabolic profiles showed that the main clearance routes were metabolism via oxidative reactions and glucuronidation. These results further strengthen the knowledge of zapnometinib with respect to the clinical development of the drug.